Research progress of flexible capacitive pressure sensor for sensitivity enhancement approaches - Li, Ruiqing; Zhou, Qun; Bi, Yin; Cao, Shaojie; Xia, Xue; Yang, Aolin; Li, Siming; Xiao, Xueliang (Sensors and actuators. A. Physical., 2021)
In this paper, three methods to improve the sensitivity of flexible capacitive pressure sensors are mainly reviewed, including (1) constructing microstructure of the dielectrics or electrodes, (2) adding conductive fillers to polymer elastomer to generate a composite dielectric, (3) introducing micro-holes into the dielectric layer. [Display omitted] •The main factors affecting the capacitance are dielectric constant and distance of electrode during compression.•Microstructure and porous materials mainly enhance the capacitance change by reducing the Young's modulus.•The composite dielectric improve the sensitivity by increasing the relative dielectric constant. Flexible pressure sensors have played a great role in acquiring information from human and automatics because of their wide use in electronic skin, soft robot, human-machine interaction and so on. Among a variety of flexible pressure sensors, capacitive pressure sensor has many advantages like simple structure, insensitive to temperature and humidity, low power consumption, etc. It is easy to fabricate such kind of pressure sensor, nevertheless, how to improve its sensitivity to broaden the high effective application has been a hotspot issue in recent years. In this paper, a large amount of research outputs on sensitivity improvement have been reviewed for flexible capacitive pressure sensor, including the aspects from introduction of performance evaluation indicators, working principle, generally used materials and capacitor structures to the methods of how to improve the sensitivity of capacitive pressure sensors. Then, the effective ways to obtain high sensitivity of pressure sensors have been compared and the development trend of flexible capacitive pressure sensor is prospected. This paper aims to provide references for the further research on the efficient fabrication of flexible capacitive pressure sensors and effective usage of such sensors in high sensitivity requirements of application areas.